Persepsi Masyarakat Terhadap Pemanfaatan Ruang di Pasar Kencar Jakarta Barat - Rafsyanjani, Muhammad Akbar; Rahmah, Adhelia Adjani; Wati, Gina Liana; Hantono, Dedi (Jurnal Arsitektur dan Perencanaan (JUARA), 2020)
Pasar Kencar is an informal market located in settlement and as a route crossing with the office center. Market conditions that are quite crowded with a strategic position make it interesting to capture people's perceptions. The research was conducted using qualitative methods and descriptive approaches. Apart from literature, interviews are the main data that can explain these perceptions. The result is a positive perception expressed by traders and buyers while a negative perception comes from road users. However, buyers also felt negative perceptions with the activities of residents around the market who played chess, gambling and chatting which blocked the road/circulation. For this reason, it is necessary to carry out further research on the impact on market sustainability.Â